Evaluation of antihypertensive medication adherence among hypertensive patients at Puskesmas Olak Kemang - Pondawinata, Marizki; Sadli, Nurul Kamilah; Astuti, Novia Tri; Chandra, M. Tri Firia (Proceedings Academic Universitas Jambi, 2025)
Background: Hypertension is a condition characterized by elevated systolic and/or diastolic blood pressure exceeding 140/90 mmHg. Medication adherence plays a crucial role in maintaining the long-term health of hypertensive patients, as non-adherence to antihypertensive therapy can lead to various complications such as stroke and even death. Objective: The study aimed to assess the level of antihypertensive medication adherence among hypertensive patients at Puskesmas Olak Kemang, especially in 2025. Methods: A descriptive study with a prospective approach was conducted, employing purposive sampling to select participants. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), which consists of eight items.Results: The results revealed that 20% of patients demonstrated high adherence, 27% moderate adherence, and 53% low adherence to antihypertensive medication at Puskesmas Olak Kemang. Conclusion: Most hypertensive patients at Puskesmas Olak Kemang exhibit at a low level of medication adherence.